Mathematics Literacy Skill on Problem Based Learning Assisted by E-Module Agito Based on Learning Motivation - Priyonggo, Hendi Widi; Wardono, Wardono; Noor Asih, Tri Sri (Universitas Negeri Semarang, 2021)
This research aims to describe mathematics literacy skill of students based on learning motivation. This mixed method research used sequential explanatory design with non-randomized control group, pretest-posttest design. This research was conducted at SMK Negeri 2 Purbalingga with population taken from X automotive light vehicle department. The technique to take the sample was purposive sampling. The findings showed various mathematics literacy skill based on learning motivation. It was shown from 4 students with high learning motivatios, 3 of them having high mathematics literacy skill and 1 moderate mathematics literacy skill. There were 23 students with moderate motivation, 1 of them having high mathematics literacy skill, 20 moderate, and 2 poor mathematics literacy skill. There were 7 poor learning motivation consisting of 5 moderate mathematics literacy skill and 2 poor skill.